GREEN BANKING DAN KINERJA BANK: MEKANISME CORPORATE GOVERNANCE - Sara Senja Setyoko; Rita Wijayanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to investigate the practice of green banking on the financial performance of banks with corporate governance mechanisms as a moderating variable. The population in this study is the banking industry that has been listed on the Indonesia Stock Exchange (IDX) in 2018-2020 with the purposive sampling method. With moderated regression analysis, this study found that green banking has an effect on bank performance. Furthermore, for the corporate governance mechanism, namely foreign ownership, the board of commissioners and the audit committee do not moderate the effect of green banking on bank performance.